Immobilization of cellulase enzyme on functionalized multiwall carbon nanotubes - Mujawar, Mubarak; Wong, J.; Tan, K.; Sahu, J.; Abdullah, E.; Jayakumar, N.; Ganesan, P. (2014)
For the past decades, the global trends in the demand of cellulase has been arisen due to its extensive range of applications in food and agriculture industry, and its potential use in the fermentation of biomass into biofuels. However, the instability, highly solubility in water, low catalytic efficiency and high cost of enzyme has become the main obstacles for the development of large scale operations and applications. In this study, cellulase enzyme was immobilized onto functionalized multiwalled carbon nanotubes (MWCNTs) via physical adsorption method to yield a stable and ease of separate enzyme. Fourier transform infrared (FTIR) spectroscopy and field emission scanning electron microscopy (FESEM) are used to confirm the successful immobilization of cellulase enzyme. In this approach, the efficiency of enzyme immobilization reaches an optimal value when 4 mg/mL enzyme concentration is used in which approximately 97% enzyme loading can be attained. Based on the UV-visible spectroscopy analysis, the optimum reaction conditions for immobilized cellulase are at pH 5 and a temperature of 50 °C. Results have revealed that MWCNT-cellulase composite still retained 52% of its cellulase activity after six cycles of the CMC analysis. This feature is beneficial to the industrial applications because of its potential to be easily separated from the end product at the end of the reaction, reuse for multiple times and allow the development of multiple enzyme reaction system.